Whole-Exome Sequencing in a Cohort of High Myopia Patients in Northwest China - Liu, Yang (Front Cell Dev Biol, 2021)
High myopia (HM) is one of the leading causes of visual impairment worldwide. In order to expand the myopia gene spectrum in the Chinese population, we investigated genetic mutations in a cohort of 27 families with HM from Northwest China by using whole-exome sequencing (WES). Genetic variations were filtered using bioinformatics tools and cosegregation analysis. A total of 201 candidate mutations were detected, and 139 were cosegregated with the disease in the families. Multistep analysis revealed four missense variants in four unrelated families, including c.904C>T (p.R302C) in CSMD1, c.860G>A (p.R287H) in PARP8, c.G848A (p.G283D) in ADAMTSL1, and c.686A>G (p.H229R) in FNDC3B. These mutations were rare or absent in the Exome Aggregation Consortium (ExAC), 1000 Genomes Project, and Genome Aggregation Database (gnomAD), indicating that they are new candidate disease-causing genes. Our findings not only expand the myopia gene spectrum but also provide reference information for further genetic study of heritable HM.